Transformative citizenship exploring its challenges to Philippine Public Administration - Manalo, Fermin P. (Philippine Journal of Public Administration, 2004)
The lack of a clear social change theory from which participation is based could render it vulnerable to manipulation by the power holders for their own interest. It can mean differently to different people especially those who have the capacity to influence the institutions that conceptualize and employ it. More importantly, any attempt to make participatory governance/development part of Public Administration (PA) discipline without enough theoretical grounding can make it a constant bone of contention, the outcome of which will be decided by whoever has the greater resources to influence research and publication. This article, then, aims to establish a development theory to provide context to the discourse of transformative citizenship and participation. It is an attempt to provide and ideological anchor to participation by conceptualizing transformative citizenship out of civic republicanism, thus, redefining some basic assumptions on citizenship such as rights, group rights, agency, identity and location among others. Further, it discusses the role of transformative citizenship in transforming Philippine Public Administration both as a discipline and as a practice. It also seeks to redefine the significant role of Philippine Public Administration in pushing for democratic governance.